Effects of propolis on warfarin efficacy - Akbay, Esin; Özenirler, Çiğdem; Çelemli, Ömür Gençay; Durukan, Ahmet Baris; Onur, Mehmet Ali; Sorkun, Kadriye (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Warfarin is commonly used to avoid thromboembolism, predominantly for cardiovascular pathologies. However, the consumption of several herbal products is not permitted during its use due to the associated interactions. Propolis is a popular phytotherapy product made by honey bees. The use of propolis has been dramatically increasing in recent times. Aim: To evaluate the possible interactions between propolis and warfarin in a mouse model with determination of the international normalized ratio (INR) values. Material and methods: CD-1 mice were employed in the experimental model. The mice were warfarinized, and propolis was administered simultaneously. The INR values were obtained. All animals were sacrificed at the end of the study. Results : The baseline INR value was 0.8 ±0.1. After 72 h, the INR value increased as expected. The INR value was 7.28 ±1.08 in the control group and 5.8 ±2.88 in the propolis group. At the end of the study, the INR value was 1.3 ±0.37. Propolis interacted with warfarin and caused a decrease in the INR value. Conclusions: Propolis interactions, especially with warfarin, should be kept in mind and further studied. Healthcare specialists should be aware of this possible interaction between warfarin and propolis and inform patients about it.